SOLUTIONS TO CURRENT ENVIRONMENTAL TREATMENTS: https://doi.org/10.5281/zenodo.14882229 - Djurayeva, Dilnoza (Journal of Contemporary World Studies, 2025)
This article will discuss the growing environmental problems in the modern world, their causes, consequences and effective ways to eliminate them. Strategies for solving environmental problems are considered based on the principles of Environmental Protection, rational use of Natural Resources and sustainable development.